An optimal control problem of the 3D viscous Camassa–Holm equations. (2nd January 2021) - The Anh, Cung; Thanh Son, Dang
Abstract : In this paper, we study an optimal control problem of the three-dimensional viscous Camassa–Holm equations in bounded domains with Dirichlet boundary conditions and a quadratic objective functional. We first prove the existence of an optimal solution. Then we establish the first-order necessary and second-order sufficient optimality conditions.